An investigation on main effects and interactions of relative age effects and playing position in female elite football in Germany - Smith, Kristy L.; Koopmann, Till; Weir, Patricia L.; Schorer, Jörg (Frontiers in Sports and Active Living, 2024)
Athlete age-grouping and age-banding has been shown to impact sport participation and athlete development. The current study examined the impact of within-year (WYEs) and between-year effects (BYEs), and their interactions with playing position, on female participation in elite German football. The sample of 1378 German first-league players revealed expected participation inequities within-year with relatively older players being over-represented and younger players being underrepresented. From a between-year perspective there were no participation differences. The interaction of WYEs and BYEs revealed an over-representation of odd-year players in Q1, and Q2 in even years. With respect to the interaction between year effects and playing position, for WYEs the expected effect was present for goalkeepers and defenders, while there was no significant interaction for BYEs. Overall, the results offer insight regarding the impact of system structure on participation, and highlight unique characteristics associated with playing positions.